European Narratives on Remote Working and Coworking During the COVID-19 Pandemic A Multidisciplinary Perspective - Akhavan, Mina; Hölzel, Marco; Leducq, Divya (PoliMI SpringerBriefs, 2023)
VIII, 153 p. 25 illus., 21 illus. in color.